Are you with me? Probing the human capacity to recognize external/internal attention in others' faces. Issue 7 (9th August 2018) - Benedek, Mathias; Daxberger, David; Annerer-Walcher, Sonja; Smallwood, Jonathan
ABSTRACT: Facial cues provide information about affective states and the direction of attention that is important for human social interaction. The present study examined how this capacity extends to judging whether attention is internally or externally directed. Participants evaluated a set of videos and images showing the face of people focused externally on a task, or internally while they performed a task in imagination. We found that participants could identify the focus of attention above chance in videos, and to a lesser degree in static images, but only when the eye region was visible. Self-reports further indicated that participants relied particularly on the eye region in their judgements. Interestingly, people engaged in demanding cognitive tasks were more likely judged to be externally focused independent of the actual focus of attention. These findings demonstrate that humans use information from the face and especially from the eyes of others not only to infer external goals or actions, but also to detect when others focus internally on their own thoughts and feelings.